RESULTS OF STUDY PERIODONTAL TISSUE CONDITION UNDER GLASS SPLINTING OF TEETH - N.P. Chuev; L.D. Chulak; Y.V. Gryzodub (Український стоматологічний альманах)
Purpose: comparative clinical assessment of oral tissues in prosthetics with ceramic constructions in the complete absence of the tooth crown.